A genome‐wide approach to children's aggressive behavior: The EAGLE consortium. Issue 5 (18th June 2015) - Pappa, Irene; St Pourcain, Beate; Benke, Kelly; Cavadino, Alana; Hakulinen, Christian; Nivard, Michel G.; Nolte, Ilja M.; Tiesler, Carla M. T.; Bakermans‐Kranenburg, Marian J.; Davies, Gareth E.; Evans, David M.; Geoffroy, Marie‐Claude; et al.
Abstract : Individual differences in aggressive behavior emerge in early childhood and predict persisting behavioral problems and disorders. Studies of antisocial and severe aggression in adulthood indicate substantial underlying biology. However, little attention has been given to genome‐wide approaches of aggressive behavior in children. We analyzed data from nine population‐based studies and assessed aggressive behavior using well‐validated parent‐reported questionnaires. This is the largest sample exploring children's aggressive behavior to date (N = 18, 988), with measures in two developmental stages (N = 15, 668 early childhood and N = 16, 311 middle childhood/early adolescence). First, we estimated the additive genetic variance of children's aggressive behavior based on genome‐wide SNP information, using genome‐wide complex trait analysis (GCTA). Second, genetic associations within each study were assessed using a quasi‐Poisson regression approach, capturing the highly right‐skewed distribution of aggressive behavior. Third, we performed meta‐analyses of genome‐wide associations for both the total age‐mixed sample and the two developmental stages. Finally, we performed a gene‐based test using the summary statistics of the total sample. GCTA quantified variance tagged by common SNPs (10–54%). The meta‐analysis of the total sample identified one region in chromosome 2 (2p12) at near genome‐wide significance (top SNP rs11126630, P  = 5.30 × 10 −8 ). The separate meta‐analyses of the two developmental stages revealed suggestive evidence of association at the same locus. The gene‐based analysis indicated association of variation within AVPR1A with aggressive behavior. We conclude that common variants at 2p12 show suggestive evidence for association with childhood aggression. Replication of these initial findings is needed, and further studies should clarify its biological meaning. © 2015 Wiley Periodicals, Inc.